Editorial: non‐viral hepatocellular carcinoma surveillance—an increasingly severe public health issue - Sun, Li‐Yang; Li, Zhen‐Li; Yang, Tian (Alimentary pharmacology & therapeutics, 2022)
LINKED CONTENT This article is linked to Toyoda et al papers. To view these articles, visit https://doi.org/10.1111/apt.17088 and https://doi.org/10.1111/apt.17139